The Effect Of Work Motivation And Carrier Development On Employee Performance Mediated By Employee Engagement At - Eggy Farizqy, Sefty; Badawi Saluy, Ahmad (DINASTI RESEARCH, 2024)
This research aims to investigate the Influence of Work Motivation, Career Development, and Employee Engagement on Employee Performance at PT Wolter Batik Nusantara using the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis method through the SmartPLS 3 program. The research collected data from employees of PT Wolter Batik Nusantara using structured questionnaires. The research sample consisted of 57 respondents selected through non-probability sampling. The analysis results showed that out of the seven hypotheses tested, five hypotheses indicated a significant positive influence between the variables under research. Work motivation and career development were found to have a significant positive influence on employee engagement, and employee engagement had a significant positive influence on employee performance. Additionally, it was found that employee engagement mediated the relationship between work motivation and employee performance, as well as between career development and employee performance. However, the other two hypotheses showed a positive but nonsignificant influence, namely work motivation on employee performance and career development on employee performance.